Investment Analysis of New Port Development Project As a Solution to Overload Problems in Long Ports - Pandi Aditiya; ahmad herison; Ika Kustiani; Amril Ma’ruf Siregar (SPATIAL: Wahana Komunikasi dan Informasi Geografi, 2019)
The increasing demand for port services at the Panjang port causes high levels of ship queues. The solution to overcome this problem is to build a new port. However, this new port construction project has not yet conducted a feasibility study. The purpose of this study is to assess the feasibility of port development in the Panjang district of Bandar Lampung in terms of investment or financial aspects. The methods are Benefit-Cost Ratio, Net Present Value, Payback Period, and Internal Rate of Return. The results of the feasibility study of the most profitable investment are in the seventh scenario, the Net Present Value (NPV) of Rp. 463,292,122,605.34, the BCR result of 1.2959, the IRR yield of 12.11% and the Payback Period (PP) occur in the year to thirty-seventh with an economic age of 60 years. The conclusion is that the construction of a new port can be a solution to overcome the overload of Panjang port.